Substituent interference on supramolecular assembly in urea gelators: synthesis, structure prediction and NMR. Issue 17 (29th March 2016) - Piana, Francesca; Case, David H.; Ramalhete, Susana M.; Pileio, Giuseppe; Facciotti, Marco; Day, Graeme M.; Khimyak, Yaroslav Z.; Angulo, Jesús; Brown, Richard C. D.; Gale, Philip A.
Abstract : –NO2 and –OCH3 substituents were shown to differ in their ability to interfere with the H-bond interactions between ureas during supramolecular gelation. Abstract : Eighteen N -aryl- N ′-alkyl urea gelators were synthesised in order to understand the effect of head substituents on gelation performance. Minimum gelation concentration values obtained from gel formation studies were used to rank the compounds and revealed the remarkable performance of 4-methoxyphenyl urea gelator15 in comparison to 4-nitrophenyl analogue14, which could not be simply ascribed to substituent effects on the hydrogen bonding capabilities of the urea protons. Crystal structure prediction calculations indicated alternative low energy hydrogen bonding arrangements between the nitro group and urea protons in gelator14, which were supported experimentally by NMR spectroscopy. As a consequence, it was possible to relate the observed differences to interference of the head substituents with the urea tape motif, disrupting the order of supramolecular packing. The combination of unbiased structure prediction calculations with NMR is proposed as a powerful approach to investigate the supramolecular arrangement in gel fibres and help understand the relationships between molecular structure and gel formation.